Addiction research centres and the nurturing of creativity: The Centre for Alcohol Policy Research (CAPR), Melbourne: a decade on. (26th November 2017) - Wilkinson, Claire; Pennay, Amy; MacLean, Sarah; Livingston, Michael; Room, Robin; Hamilton, Margaret; Laslett, Anne‐Marie; Jiang, Heng; Callinan, Sarah; Waleewong, Orratai
Abstract: Established in 2006, the Centre for Alcohol Policy Research (CAPR) is Australia's only research centre with a primary focus on alcohol policy. CAPR has four main areas of research: alcohol policy impacts; alcohol policy formation and regulatory processes involved in implementing alcohol policies; patterns and trends in drinking and alcohol problems in the population; and the influence of drinking norms, cultural practices and social contexts, particularly in interaction with alcohol policies. In this paper, we give examples of key publications in each area. During the past decade, the number of staff employed at CAPR has increased steadily and now hovers at approximately 10. CAPR has supported the development of independent researchers who collaborate on a number of international projects, such as the Alcohol's Harm to Others study which is now replicated in approximately 30 countries. CAPR receives core funding from the Foundation for Alcohol Research and Education, and staff have been highly successful in securing additional competitive research funding. In 2016, CAPR moved to a new institutional setting at La Trobe University and celebrated 10 years of operation.